The cleavage site preference of the porcine pepsin on the N-terminal α1 chain of bovine type I collagen: a focal analysis with mass spectrometry. Issue 3 (4th March 2017) - Qian, Jun; Ito, Shinji; Satoh, Junko; Geng, Hongmin; Tanaka, Keisuke; Hattori, Shunji; Kojima, Kenji; Takita, Teisuke; Yasukawa, Kiyoshi
Abstract: Bovine type I collagen consists of two α1 and one α2 chains, containing the internal triple helical regions and the N- and C-terminal telopeptides. In industries, it is frequently digested with porcine pepsin to produce a triple helical collagen without the telopeptides. However, the digestion mechanism is not precisely understood. Here, we performed a mass spectrometric analysis of the pepsin digest of the N-terminal telopeptide pQLSYGYDEKSTGISVP (1–16) in the α1 chain. When purified collagen was digested, pQLSYGY (1–6) and pQLSYGYDEKSTG (1–12) were identified, while DEKSTG (7–12) was not. When the N-terminal telopeptide mimetic synthetic peptide pQLSK(MOCAc)GYDEKSTGISK(Dnp)P-NH2 was digested, pQLSK(MOCAc)GYDEKSTG (1–12) and ISK(Dnp)P-NH2 (13−16) were readily identified, pQLSK(MOCAc)GY (1−6) and DEKSTGISK(Dnp)P-NH2 (7−16) were weakly detected, and DEKSTG (7–12) was hardly identified. These results suggest that pepsin preferentially cleaves Tyr6–Asp7 and less preferentially Gly12–Ile13. They also suggest that the former cleavage requires native collagen structure, while the latter cleavage does not. Graphical abstract: : Pepsin preferentially cleaves Tyr6–Asp7 and less preferentially Gly12–Ile13. The former cleavage requires native collagen structure, while the latter cleavage does not.